Child Punishment Versus the Principle of Non-Discrimination in the Perspective of Human Rights: A Legal Comparison Between Indonesia and Vietnam - Widowati; Vu Le Giang (Universitas Negeri Surabaya, 2025)
Criminalization of children is a phenomenon that occurs in almost every country in the world and is relevant to the existence of children's rights as part of human rights. This research aims to analyze the criminalization of children in relation to the principle of non-discrimination in the 1989 Convention on the Rights of the Child, while also making a legal comparison with Indonesia and Vietnam regarding the regulation of child criminalization policies. This research is a juridical-normative legal study using a comparative, conceptual, and legislative approach. The research findings affirm that the criminalization of children fundamentally contradicts the principles of human rights, particularly the principle of non-discrimination in the 1989 Convention on the Rights of the Child. Therefore, the juvenile justice system must be designed as a form of special treatment that emphasizes rehabilitation and the protection of children's rights, rather than mere punishment. Child sentencing policies in Indonesia and Vietnam essentially share similarities in prioritizing the principle of the best interests of the child and the application of diversion as an alternative to sentencing. However, differences are evident in the legal structure and its implementation, where Indonesia has a specific law that comprehensively regulates the juvenile justice system, while Vietnam is still in the stage of legal reform through a draft law that emphasizes sentence reduction and the application of community-based diversion. The suggestions and recommendations from this study are that the government and policy makers in countries, especially Indonesia and Vietnam, are advised to continue to develop and strengthen the juvenile criminal justice system that is oriented towards rehabilitation, not punishment, in accordance with the principle of non-discrimination in the 1989 Convention on the Rights of the Child. Keywords: Children's Rights, Human Rights, Juvenile Justice.